Tea Party in Wonderland - Finnegan, Delphine; Gifford, Chris; Miller, Victoria (Victoria H.) (New York : Random House, 2014)
Dora the Explorer goes down the rabbit hole and discovers the exciting magical world of Wonderland.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile fiction; Dora the Explorer (Fictitious character) -- Fiction; Fantasy